Embryonic Stem Cells Do Not Stiffen on Rigid Substrates - Poh, Yeh-Chuin (The Biophysical Society, 2010)
It has been previously established that living cells, including mesenchymal stem cells, stiffen in response to elevation of substrate stiffness. This stiffening is largely attributed to the elevation of the tractions at the cell base that is associated with increases in cell spreading on more-rigid substrates. We show here, surprisingly, that mouse embryonic stem cells (ESCs) do not stiffen when substrate stiffness increases. As shown recently, these cells do not increase spreading on more-rigid substrates either. However, these ESCs do increase their basal tractions as substrate stiffness increases. We conclude that these ESCs exhibit mechanical behaviors distinct from those of mesenchymal stem cells and of terminally differentiated cells, and decouple its apical cell stiffness from its basal tractional stresses during the substrate rigidity response.